2014
DOI: 10.13005/ojc/300410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steric Hindrance on The Antioxidant Activity of Some Schiff Base Ligands And Their Copper(II) Complexes

Abstract: Herein we report the synthesis, characterization and antioxidant activity of the Schiff base ligands (E)-4-bromo-2-((2-piperazine-1-yl)ethylimino)methylphenol and 2,2'-(1E,1E')-cyclohexane-1,2-diylbis(azan-1-yl-1-ylidene))bismethan-1-yl-1-ylidene)bis (4-bromophenol) and their complexes of copper (II) ion. Antioxidant activities of the copper complexes were studied by ferric reducing antioxidant power (FRAP) assay according to the procedure reported by Benzie and Strain 1 which considered the reduction of ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Their activity was markedly lower compared to the standard antioxidant, and differences in their activity were observable only at the highe concentrations tested (Figure 4). Several other Cu(II) complexes with various N-heterocy clic ligands displayed similar properties, which have been described in the literature [39][40][41]. The results showed that the Cu-L1 complex displayed a concentration-dependent, low-to-moderate radical scavenging activity (5-34%) when compared to ascorbic acid (AA, 24-86%).…”
Section: Determination Of Antioxidant Activitysupporting
confidence: 71%
“…Their activity was markedly lower compared to the standard antioxidant, and differences in their activity were observable only at the highe concentrations tested (Figure 4). Several other Cu(II) complexes with various N-heterocy clic ligands displayed similar properties, which have been described in the literature [39][40][41]. The results showed that the Cu-L1 complex displayed a concentration-dependent, low-to-moderate radical scavenging activity (5-34%) when compared to ascorbic acid (AA, 24-86%).…”
Section: Determination Of Antioxidant Activitysupporting
confidence: 71%
“…is finding has already been underlined through the assessment of the radical scavenging activity of juglone and its derivatives done by Jin [27]. e 0.299 eV drop in IP obtained after a replacement of the hydrogen atom attached to C 5 carbon atom of F 0 by a great aliphatic substituent (D 0 ) exhibits the influence of the steric hindrance on the antioxidant activity observed during the study of Schiff base ligands and their copper (II) complexes [28]. A 0.363 eV similar decrease in IP (E 0 ) has been yielded by substituting the hydrogen atom of hydroxide group bound to C 4 carbon atom of (F 0 ) by this same aliphatic substituent.…”
Section: Antioxidant Propertiesmentioning
confidence: 79%
“…e difference in IP for La 2 and La 6 equal to 4.776 kJ/mol exhibits the effect of steric hindrance on antioxidant activity. e alteration of the antioxidant activity of some Schiff base ligands and their copper (II) complexes by this steric hindrance has been reviewed by Salga et al [44]. Similarly, Sun et al have experimentally demonstrated that the antioxidant activity of flavonoids isolated from Hebei balmy chrysanthemum is sensitive to the steric hindrance of glucoside [45].…”
Section: Electron Transfer Mechanismmentioning
confidence: 99%